The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.31616/asj.2019.0046
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the Association between Disc Degeneration Changes on Imaging and Low Back Pain: A Review Article

Abstract: Low back pain (LBP) is a major health issue resulting in a huge economic burden on the community. It not only increases the medical costs directly, but also raises the disability and loss of productivity in the general population. Symptoms include local pain over the spinal area, pain radiating to the lower leg, stiffness, and muscle tension. LBP is strongly linked with intervertebral disc degeneration that is further associated with the disruption of the complex anatomy of nucleus pulposus, annulus fibrosus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 66 publications
1
40
1
3
Order By: Relevance
“…Interestingly, these significant relationships between DH severity and cytokine levels were present in subjects with chronic symptoms, but did not hold for those with acute symptoms. Not surprisingly, we did not observe significant differences in serum cytokines with respect to disease severity as classified by Pfirrmann grade, consistent with prior findings 25,29 . Indeed, MRI signal grading of degeneration does not correlate to functional impairment or pain 30 .…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, these significant relationships between DH severity and cytokine levels were present in subjects with chronic symptoms, but did not hold for those with acute symptoms. Not surprisingly, we did not observe significant differences in serum cytokines with respect to disease severity as classified by Pfirrmann grade, consistent with prior findings 25,29 . Indeed, MRI signal grading of degeneration does not correlate to functional impairment or pain 30 .…”
Section: Discussionsupporting
confidence: 91%
“…The evidence for the presence of Modic changes as an association to low back pain is conflicting (11,(209)(210)(211)(212)(213)(214). Two reviews have found Modic type 1 changes to be relatively correlated to low back pain (211,212). Modic type 1 was also observed in a larger proportion at level L4-L5 and particularly level L5-S1 among the cases compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…6 With the advent of MRI, the complex relationship between disc, vertebral body, end plates and facet joints; as well as their individual roles in the pathogenesis of LBP have received tremendous attention. 7 The disc is avascular with sparse nerve distribution and lacks a strong physiological basis as a primary pain generator. 8 Over years, the attention has therefore shifted to other anatomical structures like endplates to explain the etiological basis of LBP.…”
Section: Low Back Pain and Historic Background Of MCmentioning
confidence: 99%